IMPLEMENTATION OF LAW NO. 17 OF 2023 IN THE IMPLEMENTATION OF SOCIAL SERVICE AT THE AVALOKITESVARA VIHARA, STABAT - Lenny; Muhammad Arif Sahlepi; Irsyam Risdawati (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Health services are a fundamental right of every citizen as guaranteed by Law Number 17 of 2023 on Health. However, disparities in access to health services still persist, particularly in remote areas and among low-income populations. Religious institutions such as Vihara Avalokitesvara Stabat play an important role in expanding access to healthcare through social health service activities. This study aims to analyze the implementation of Law Number 17 of 2023 in the conduct of social health services at Vihara Avalokitesvara Stabat, particularly in terms of Standard Operating Procedures (SOP) and informed consent. The research employs a normative juridical approach using secondary data consisting of primary, secondary, and tertiary legal materials, which are analyzed through qualitative descriptive methods. The results indicate that the implementation of social health services has a strong legal basis in Article 14 and Article 35 paragraph (1) of Law Number 17 of 2023. The implementation of SOPs and informed consent at Vihara Avalokitesvara Stabat shows substantial compliance with healthcare service standards, with the SOP structure covering eight comprehensive components and the informed consent form containing the essential elements of medical ethics. The social service activity conducted on October 26, 2025 served 50 participants from various regions. The challenges encountered include limited understanding of regulations, resource constraints, and coordination issues. The recommendations include the development of technical guidelines, regular training programs, strengthened coordination, and the development of an online reporting system to improve the quality of community-based healthcare services.